2
$\begingroup$

If the normal to the point P on the ellipse intersects the major and minor axis and $G$ and $g$, then find the relation between $CG$, $Cg$, $a$ and $b$, where C is centre

The normal at $P(x_1,y_1)$ is $$\frac{a^2x}{x_1}-\frac{b^2y}{y_1}=a^2-b^2$$

The intercepts will be $$CG=\frac{x_1(a^2-b^2)}{a^2}$$ $$Cg=\frac{y_1(a^2-b^2)}{b^2}$$

Unfortunately I am not able to eliminate the terms $x_1$ and $y_1$. How should I do it?

$\endgroup$
  • 1
    $\begingroup$ $(x_1,y_1)$ is on the ellipse, so ... $\endgroup$ – Blue Apr 7 '20 at 13:33
3
$\begingroup$

We know that $(x_1,y_1)$ must lie on the ellipse, so, we have: $$\frac{x_1^2}{a^2}+\frac{y_1^2}{b^2}=1 \leftrightarrow y_1^2=b^2\left(1-\frac{x_1^2}{a^2}\right)$$ Substituing, we obtain: $$Cg^2=\frac{b^2\left(1-\frac{x_1^2}{a^2}\right)(a^2-b^2)^2}{b^4}$$ While $CG^2$ is: $$CG^2=\frac{x_1^2(a^2-b^2)^2}{a^4}\leftrightarrow x_1^2=\frac{CG^2\cdot a^4}{(a^2-b^2)^2} $$ Substituing again, you arrive at: $$Cg^2=\frac{b^2\left(1-\frac{CG^2\cdot a^4}{a^2(a^2-b^2)^2}\right)(a^2-b^2)^2}{b^4} \rightarrow Cg^2=\frac{(a^2-b^2)^2-CG^2\cdot a^2}{b^2}$$ From here, it's very simple. In fact: $$Cg=\sqrt{Cg^2}=\sqrt{\frac{(a^2-b^2)^2-CG^2\cdot a^2}{b^2}}=\frac{\sqrt{(a^2-b^2)^2-CG^2\cdot a^2}}{b}$$

Note that, as @Blue suggested, you can rewrite the relation for $Cg^2$ as: $$\frac{Cg^2}{a^2} + \frac{CG^2}{b^2} =\frac{ (a^2-b^2)^2}{a^2b^2}$$ This follows from here: $$Cg^2=\frac{(a^2-b^2)^2-CG^2\cdot a^2}{b^2} \leftrightarrow Cg^2b^2-CGa^2=(a^2-b^2)^2 \leftrightarrow \frac{Cg^2}{a^2} + \frac{CG^2}{b^2} =\frac{ (a^2-b^2)^2}{a^2b^2}$$

$\endgroup$
  • $\begingroup$ +1. I probably would have manipulated your arrived-at relation into $$\frac{Cg^2}{a^2} + \frac{CG^2}{b^2} =\frac{ (a^2-b^2)^2}{a^2b^2}$$ to maximize symmetry. $\endgroup$ – Blue Apr 7 '20 at 13:50
  • $\begingroup$ @Blue: I will add this in the answer. $\endgroup$ – Matteo Apr 7 '20 at 13:54
  • $\begingroup$ Done. Thanks!!! $\endgroup$ – Aditya Apr 7 '20 at 17:29
  • 1
    $\begingroup$ @Aditya: none, thanks. I like a lot problems on conic section, especially ellipse, so I really like this questions. $\endgroup$ – Matteo Apr 7 '20 at 17:30
2
$\begingroup$

In the same vein as Matteo’s answer but with, I think, much less work: From your calculations we have $$x_1 = {a^2\over a^2-b^2}{CG} \\ y_1 = {b^2\over a^2-b^2}{Cg}.$$ The point $(x_1,y_1)$ lies on the ellipse, therefore $${x_1^2\over a^2} + {y_1^2\over b^2} = \frac1{a^2}\left({a^2\over a^2-b^2}{CG}\right)^2 + \frac1{b^2}\left({b^2\over a^2-b^2}{Cg}\right)^2 = 1$$ and after some straightforward rearrangement, we end up with $${{Cg}^2\over a^2}+{{CG}^2\over b^2} = {(a^2-b^2)^2\over a^2b^2}.$$

$\endgroup$
1
$\begingroup$

WLOG any point on the ellipse $P(a\cos t,b\sin t)$

Using https://www.askiitians.com/iit-jee-coordinate-geometry/tangent-and-normal.aspx#how-do-you-find-the-equation-of-the-normal-to-an-ellipse ,

the equation of the normal $$ax\sec t-by\csc t=a^2-b^2$$

$G: \dfrac{(a^2-b^2)\cos t}a,0$

$g: 0, -\dfrac{(a^2-b^2)\sin t}b$

$$a\cdot CG=|(a^2-b^2)\cos t|,|\cos t|=?$$

Similarly

$$b\cdot CG=|(a^2-b^2\sin t|,|\sin t|=?$$

Eliminate $t$ using $\cos^2t+\sin^2t=1$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.